Non-invasive sensing techniques for glucose detection: a review - Jamal Al-Nabulsi; Hamza Abu Owida; Jumana Ma’touq; Sabrina Matar; Esraa Al-Aazeh; Abdelqader Al-Maaiouf; Abdullah Bleibel (Bulletin of Electrical Engineering and Informatics, 2022)
Diabetes is becoming more prevalent over the world, with approximately 7.8 million new cases diagnosed each year. The most crucial aspect of diabetes therapy is frequent glucose monitoring; the one and only way diabetics can maintain healthy blood sugar standard is through diet and exercise. Blood glucose monitoring techniques have gone through massive transformations over the past few years. Non-invasive procedures outperform invasive and minimally invasive ones in terms of inconvenience, pain, and recovery time. Thus, this review aims to explore the latest tools for non-invasive glucose monitoring sensors and techniques. The study showed that non-invasive techniques such as optical and non-optical techniques are better than invasive techniques in terms of accuracy, reliability, repeatability, and ease of use. The study also uncovered that the photoacoustic spectroscopy and ultrasonic techniques have room for further development and advancement considering their flexible nature. The work also proved that the ultrasonic technique is the most promising approach, in conclusion.